1998
DOI: 10.1002/(sici)1097-4571(199806)49:8<693::aid-asi4>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning approach to inductive query by examples: An experiment using relevance feedback, ID3, genetic algorithms, and simulated annealing

Abstract: Information retrieval using probabilistic techniques has attracted significant attention on the part of researchers in information and computer science over the past few decades. In the 1980s, knowledge‐based techniques also made an impressive contribution to “intelligent” information retrieval and indexing. More recently, information science researchers have turned to other newer inductive learning techniques including symbolic learning, genetic algorithms, and simulated annealing. These newer techniques, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Chen et al . (1998) did apply machine learning techniques for selecting query terms, but it was done in the context of relevance feedback retrieval. More recently, Bendersky and Croft (2008) developed an approach to identify the most important concepts in verbose ad hoc retrieval queries.…”
Section: Related Workmentioning
confidence: 99%
“…Chen et al . (1998) did apply machine learning techniques for selecting query terms, but it was done in the context of relevance feedback retrieval. More recently, Bendersky and Croft (2008) developed an approach to identify the most important concepts in verbose ad hoc retrieval queries.…”
Section: Related Workmentioning
confidence: 99%
“…The builder mapping B is implemented by using the genetic programming (GP) technique proposed by Malo et al [20] that extends the Inductive Query By Example (IQBE) paradigm of Smith and Smith [21] and Chen et al [22]. There, the idea is to use the relevance information collected from the user as fitness cases to find the query expression that best separates relevant from irrelevant document examples.…”
Section: B Wiki-sr Modelmentioning
confidence: 99%
“…Although simple in this implementation, we believe that the optimization approach prevents the search from narrowing too rapidly. Naturally, evaluations would need to be done on the appropriate optimization algorithm to most effectively select terms, although Chen et al (1998) have shown the three most well known optimization algorithms all perform equally well.…”
Section: Relevance Feedbackmentioning
confidence: 99%